Endoplasmic reticulum stress‐dependent autophagy inhibits glycated high‐density lipoprotein‐induced macrophage apoptosis by inhibiting CHOP pathway - Tian, Hua (J Cell Mol Med, 2019)
This study was designed to explore the inductive effect of glycated high‐density lipoprotein (gly‐HDL) on endoplasmic reticulum (ER) stress‐C/EBP homologous protein (CHOP)‐mediated macrophage apoptosis and its relationship with autophagy. Our results showed that gly‐HDL caused macrophage apoptosis with concomitant activation of ER stress pathway, including nuclear translocation of activating transcription factor 6, phosphorylation of protein kinase‐like ER kinase (PERK) and eukaryotic translation initiation factor 2α, and CHOP up‐regulation, which were inhibited by 4‐phenylbutyric acid (PBA, an ER stress inhibitor) and the gene silencing of PERK and CHOP. Similar data were obtained from macrophages treated by HDL isolated from diabetic patients. Gly‐HDL induced macrophage autophagy as assessed by up‐regulation of beclin‐1, autophagy‐related gene 5 and microtubule‐associated protein one light chain 3‐II, which were depressed by PBA and PERK siRNA. Gly‐HDL‐induced apoptosis, PERK phosphorylation and CHOP up‐regulation were suppressed by rapamycin (an autophagy inducer), whereas aggravated by 3‐methyladenine (an autophagy inhibitor) and beclin‐1 siRNA. Administration of diabetic apoE(−/−) mice with rapamycin attenuated MOMA‐2 and CHOP up‐regulation and apoptosis in atherosclerotic lesions. These data indicate that gly‐HDL may induce macrophage apoptosis through activating ER stress‐CHOP pathway and ER stress mediates gly‐HDL‐induced autophagy, which in turn protects macrophages against apoptosis by alleviating CHOP pathway.